ChemInform Abstract: Diastereo‐ and Enantioselective Intramolecular 1, 6‐C—H Insertion Reactions of α‐Diazo Esters Catalyzed by Chiral Dirhodium(II) Carboxylates. Issue 28 (July 2015) - Ito, Motoki; Kondo, Yuji; Nambu, Hisanori; Anada, Masahiro; Takeda, Koji; Hashimoto, Shunichi
Abstract The first catalytic asymmetric 1, 6‐C—H insertion reaction of α‐diazo esters catalyzed by 1 mol % of a chiral Rh‐complex is developed which provides facile access to optically active oxygen‐containing six‐membered cyclic core structures of biologically active natural products and pharmaceutical agents.